A Thematic Review of the Influences of Classroom Environment on Student’s Learning Outcomes in EFL Context - Akib Jamil (Universitas Majalengka, 2025)
The classroom environment has a significant impact on learning English as a foreign language (EFL), especially in higher education settings. This article aims to explore the ways in which classroom management style, teacher-student interaction dynamics, physical layout, emotional tone, and, finally yet importantly, institutional policies can all affect language-learning outcomes in EFL classrooms. By focusing on postsecondary education, the review closes a significant gap in the literature. Based on 51 peer-reviewed articles published between 2017 and 2025, a qualitative thematic review was conducted. Patterns essential to every study were found using the thematic analysis method developed by Braun and Clarke (2006). Only empirical research pertaining to EFL classroom settings that met strict acceptance standards was included in the review. Common themes were found in the physical environment, motivation, engagement, emotional safety, technology integration, and institutional support after a thematic coding framework was tested. The results show that frequent teacher-student interactions, flexible classroom layouts, high emotional support, and autonomy-supportive teaching techniques are associated with increased motivation, self-assurance, and active language use among EFL learners. On the other hand, stressful situations and strict, teacher-centred lessons result in lower accomplishments and disengagement. Language learning seems to be significantly influenced by the idea of emotional safety, or the ability to take chances without fear of repercussion. These findings suggest that classroom design and instructional techniques need to be reviewed by educators and educational institutions alike (Hasan et al., 2024a). Improving learning outcomes and encouraging long-term success for EFL learners requires creating pedagogically engaging classrooms, emotionally safe, and physically comfortable.